California notes. - Turrill, Charles B. (Charles Beebe), 1854-1927. (San Francisco, E. Bosqui & co., 1876)
Charles Beebe Turrill (1854-1927) was a California historian and promoter. California notes (1876) is a guide for travellers, offering details of the state's weather, geology, and vegetation as well as recommended travel routes, historical notes, business statistics, and sightseeing tips for visitors to San Francisco, Stockton, Calaveras County and its mammoth trees and caves, the gold mining district, and the Yosemite Valley.
At head of title: First volume.
No more published.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; Urbanization -- California; Real estate development -- California; Mines and mineral resources -- California; Agriculture -- California; Business -- California